A new bee-mimicking stiletto fly (Therevidae) from China discovered on iNaturalist - Winterton, Shaun L. (Zootaxa, 2020)
The Chinese stiletto fly fauna is poorly known, with few species previously described and no endemic genera. A new genus and species of charismatic stiletto fly is described from northern China. Although the species was previously known from a poorly preserved specimen, the true form of this apparent bumble bee-mimic was not known until images of a live individual were discovered amongst photographs posted on iNaturalist, an online citizen scientist and biodiversity social network.